Self Disclosure Pada Komunikasi Generasi Z - Apriyanti, Eka; Sari, Sapta; Dianthi, Martha Heriniazwi (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Instagram with its features has encouraged Generation Z to self-disclose. Self-disclosure on Instagram has a unique form of communication. Individuals can choose to reveal aspects of their personal lives with varying degrees of openness. The purpose of this research is to find out how Generation Z discloses information about themselves (self-disclosure) which is often hidden as a form of communication through Instagram social media. The type of research used by researchers is qualitative research with an analytical approach in accordance with DeVito's Theory. The sampling method uses purposive sampling method. The result of the study is that self-disclosure by informants tends to be often done to people who are known according to the amount aspect in DeVito's Theory. The five informants have fulfilled the valence aspect of self-disclosure by conveying positive or negative expressions on Instagram through photo and video content. The five informants' self-disclosure has fulfilled the accuracy/honesty aspect of DeVito's Theory where self-disclosure actions are mostly based on existing reality. The five informants have fulfilled the intention aspect of DeVito's theory, namely conveying their intentions and goals even though the application is different. Each informant has a different level of familiarity and depth of self-disclosure material, depending on who the self-disclosure is disclosed to. This is in line with the intimacy aspect of DeVito's theory. Self disclosure made by the five informants on Instagram social media has fulfilled 5 aspects of DeVito's theory, namely amount, valence, accuracy/honesty, intention and intimacy.